Perlindungan Hukum bagi Bidan Praktik Mandiri dalam Menjalankan Praktik Kebidanan - Rezky Fransilya Sumbung (Jurnal Hukum dan Etika Kesehatan, 2021)
Legal Protection for Practicing Midwives is regulated in Law Number 36 Year 2014 concerning to Health Workers, Articles 57 and 75. Article 57 stipulates that: "personnel in carrying out practices have the right to legal protection as long as they carry out their duties in accordance with professional standards, professional service standards, and standard operating procedures." Article 75 stipulates that: "in carrying out the practice, health workers have the right to legal protection in accordance with statutory provisions". Likewise in Permenkes 1464 / Menkes / Per / X of 2010 concerning Permits and Practices of Midwives Article 19 stipulates that: "in carrying out practice / work, midwives have the right to obtain legal protection in carrying out practice / work as long as it is in accordance with standards". This paper will explain about the authority of midwives in implementing midwife practices and legal protection for midwives in implementing independent midwives. The purpose of this paper is to analyze the authority of independent practice midwife services and to examine the form of legal protection for independent practicing midwives in the implementation of independent practice midwives. The author uses a research method with a normative juridical type and the approach issue using statutory approach, a conceptual approach and a comparative approach.